THE ROLE OF CONSUMER TRUST IN MEDIATING THE INFLUENCE OF BRAND IMAGE ON DECISIONS TO PURCHASE LOCAL FASHION BRAND PRODUCTS AEROSTREET(Study of Tokopedia Marketplace Consumers in Denpasar City) - Ni Wayan Ratna Pradnyana Dewi; Ni Ketut Seminari (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
The rapid development of fashion is accompanied by the rapid circulation of information and the flow of globalization entering a country. Various fashion trends emerge, making changes in trends have an impact on a person's lifestyle. This can be a consideration for fashion companies to pay more attention to factors that can provide many benefits to the sale of their fashion products through purchasing decisions. One of the factors that influences purchasing decisions is a positive brand image, because having a strong brand image can cause the brand to stick in the minds of consumers. This research aims to explain the role of consumer trust as a mediator in the influence of brand image on purchasing decisions for local fashion brand Aerostreet products. The research was conducted on Tokopedia Marketplace consumers in Denpasar City who had previously purchased Aerostreet fashion products with a sample size of 100 respondents. Data collection was carried out through an online survey with a questionnaire tool in the form of a Google form. The analysis technique uses path analysis, Sobel test, and VAF test with the help of the SPSS for Windows program. The results of this research show that brand image has a positive and significant effect on purchasing decisions, brand image has a positive and significant effect on consumer trust, consumer trust has a positive and significant effect on purchasing decisions, and consumer trust plays a significant role in mediating the influence of brand image on purchasing decisions. The implications of this research can strengthen previous research and become a reference for Aerostreet in maintaining product quality and the benefits consumers feel about the Aerostreet brand.